2011
DOI: 10.1002/hep.24590
|View full text |Cite
|
Sign up to set email alerts
|

Multipotent stem/progenitor cells in human biliary tree give rise to hepatocytes, cholangiocytes, and pancreatic islets

Abstract: Multipotent stem/progenitors are present in peribiliary glands of extrahepatic biliary trees from humans of all ages and in high numbers in hepato-pancreatic common duct, cystic duct, and hilum. They express endodermal transcription factors (e.g., Sox9, SOX17, FOXA2, PDX1, HES1, NGN3, PROX1) intranuclearly, stem/progenitor surface markers (EpCAM, NCAM, CD133, CXCR4), and sometimes weakly adult liver, bile duct, and pancreatic genes (albumin, cystic fibrosis transmembrane conductance regulator [CFTR], and insul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
364
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 295 publications
(386 citation statements)
references
References 31 publications
21
364
0
1
Order By: Relevance
“…Pre-clinical studies have reinforced this thought process, where immunohistochemical studies from BC samples revealed phenotypic traits of cholangiocytes and progenitor cells consistent with their anatomic sites of origin, confirming the heterogeneity between the three groups (2). Progenitor cells from the canals of Hering have been identified in IHCC, while those within the peribiliary glands have been identified in EHCC and gallbladder cancers, respectively (2)(3)(4)(5). Furthermore, the increased availability of next-generation sequencing panels has facilitated this thought process by allowing us to understand the tumor somatic variants and genomic heterogeneity between the three groups.…”
Section: Introductionmentioning
confidence: 76%
“…Pre-clinical studies have reinforced this thought process, where immunohistochemical studies from BC samples revealed phenotypic traits of cholangiocytes and progenitor cells consistent with their anatomic sites of origin, confirming the heterogeneity between the three groups (2). Progenitor cells from the canals of Hering have been identified in IHCC, while those within the peribiliary glands have been identified in EHCC and gallbladder cancers, respectively (2)(3)(4)(5). Furthermore, the increased availability of next-generation sequencing panels has facilitated this thought process by allowing us to understand the tumor somatic variants and genomic heterogeneity between the three groups.…”
Section: Introductionmentioning
confidence: 76%
“…23 Sox9 is an endodermal transcription factor, and EpCAM is a stem/progenitor cell surface marker. [24][25][26] Immunostaining showed that CK19 and OV6 were expressed in proliferated cholangiocytes after BDL treatment (Figures 2a and b). Co-immunostaining revealed that OV6/CK19, Sox9/CK19 were extensively co-expressed in proliferated cholangiocytes (Figures 2c and d) and immunoblotting confirmed CK19, OV6, Sox9, and EpCAM protein gradually increased (Figure 2e).…”
Section: Hpcs Are a Source Of Proliferated Cholangiocytesmentioning
confidence: 99%
“…Известно, что активированные овальные прогениторные клетки, локализованные в нишах канальцев Геринга, при делении дают потомст-во 2-х фенотипически разных линий клеток пе-чени, одна из которых дифференцируется в ге-патоциты, а вторая -в холангиоциты [24]. В дифференциации прогениторных клеток печени активную роль выполняют Notch-сигналы и Wnt-белки: при билиарной дифференцировке экспрессия Jagged 1 миофибробластами усили-вает Notch-сигнализацию в прогениторных клетках и их дифференцировку в холангиоциты; при снижении Notch сигналов и активации сек-реции Wnt3a макрофагами прогениторные клет-ки параллельно дифференцируются в гепатоци-ты [25].…”
Section: Morphologia • 2017 • том 11 • № 4 • морфологіяunclassified